"Mama, I can't breathe." Louisville's dirty air has steep medical and economic costs. Issue 8 (2nd August 2020) - Gilderbloom, John Hans; Squires, Gregory D.; Meares, Wesley L.
ABSTRACT: The calls for greater racial equity also means cleaning up the air, water, and soil. Poor people needlessly suffer more in Louisville than the same low-income people in West Coast cites. If we adopted the same tough, environmental regulations as our West Coast Counterparts West Louisville would surely bloom instead of slowly die. The unfairness between black and white neighbourhoods is stark and vivid. As the great urbanist, Jane Jacobs, once said: "everyone hungers for a first class neighbourhood for both pride and dignity … nobody wants a second class neighborhood." First class neighbourhoods are safe, healthy, sustainable, and prosperous. It is a human right; a Worldwide right.